2023
DOI: 10.1063/5.0129724
|View full text |Cite
|
Sign up to set email alerts
|

In situ x-ray absorption investigations of a heterogenized molecular catalyst and its interaction with a carbon nanotube support

Abstract: A highly active heterogenized molecular CO2 reduction catalyst on a conductive carbon support is investigated to identify if its improved catalytic activity can be attributed to strong electronic interactions between catalyst and support. The molecular structure and electronic character of a [Re+1(tBu-bpy)(CO)3Cl] (tBu-bpy = 4,4′-tert-butyl-2,2′-bipyridine) catalyst deposited on multi-walled carbon nanotubes (CNT) are characterized using Re L3-edge X-ray absorption spectroscopy (XAS) under electrochemical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The absence of measurable Faradaic waves in CV has been reported elsewhere for molecular electrocatalysts covalently coupled to and physiosorbed to graphitic surfaces. ,, In certain covalently attached systems, redox silence is thought to arise from strong electronic coupling between the electrode and molecular catalyst. , On the other hand, a recent report using in situ X-ray adsorption to probe the Re-oxidation state in Re(tbu-bpy)(CO) 3 Br adsorbed on MWCNT demonstrated that strong electronic coupling is not a requirement for redox silence to be observed in physiosorbed molecular species …”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The absence of measurable Faradaic waves in CV has been reported elsewhere for molecular electrocatalysts covalently coupled to and physiosorbed to graphitic surfaces. ,, In certain covalently attached systems, redox silence is thought to arise from strong electronic coupling between the electrode and molecular catalyst. , On the other hand, a recent report using in situ X-ray adsorption to probe the Re-oxidation state in Re(tbu-bpy)(CO) 3 Br adsorbed on MWCNT demonstrated that strong electronic coupling is not a requirement for redox silence to be observed in physiosorbed molecular species …”
Section: Resultsmentioning
confidence: 95%
“…Electrodes of catalysts 1−5 were prepared according to a method previously reported by our lab. 12 Briefly, an equal part (mg/mg) mixture of Mn(bpy-R)(CO) 3 Br and MWCNT was suspended in isopropyl alcohol (IPA) with sonication to produce an ink that was spray-coated onto carbon fiber paper and dried at 80 °C to produce an electrode. The preparation of samples was done in the dark to minimize the light exposure and degradation of the Mn catalyst.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations